2011
DOI: 10.1590/s1516-89132011000400007
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant activity of a sulfated polysaccharide isolated from the green seaweed Caulerpa cupressoides

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 40 publications
9
33
2
Order By: Relevance
“…The heparin-like anticoagulant activities of SPs from marine algae have been universally recognized [60,61]. The anticoagulant activity of SPs is likely the most important aspect of extensive explorations of marine algae in the medical field.…”
Section: Biological Activities Of Sulfated Polysaccharides Of Greementioning
confidence: 99%
“…The heparin-like anticoagulant activities of SPs from marine algae have been universally recognized [60,61]. The anticoagulant activity of SPs is likely the most important aspect of extensive explorations of marine algae in the medical field.…”
Section: Biological Activities Of Sulfated Polysaccharides Of Greementioning
confidence: 99%
“…According to Fonseca et al (2008) and Mourão (2015), slight differences in the proportion and/or distribution of sulfated residues in polysaccharide chains could be critical for the interaction of proteases, inhibitors and activators of the coagulation system, resulting in a distinct pattern of anti-and pro-coagulant effects and in antithrombotic action. Regarding the PT test, treatment of the human plasma with crude SPs extracts (1 mg mL -1 ) did not modify the normal values in the extrinsic coagulation pathway (data not shown - Rodrigues et al, 2011). …”
Section: Resultsmentioning
confidence: 88%
“…(p > 0.05), but 9-to 12-fold lower than that of UHEP, which had a marked increment on intrinsic system already at low concentrations. Using these same macroalgae species, Rodrigues et al (2011;2012b) recorded effects of 24.62 and 72.66 IU mg -1 from major polysaccharidic fractions, respectively. The tested samples of A. muscoides and C. racemosa showed modest inhibitory effects corresponding to 2.81 and 7.88 IU mg -1 , respectively, as described by Quinderé et al (2014) and Rodrigues et al (2016b;2012c), who previously reported reduced anticoagulation induced by their SPs extracted with papain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations